2006
DOI: 10.1111/j.1600-0609.2006.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of interferon‐alpha administration after 2‐deoxycoformycin in the treatment of hairy cell leukemia patients

Abstract: From our data there does not appear to be any significant role for IFN-alpha in improving the proportion and the duration of CR in HCL patients previously treated with DCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our results are similar to those from three previous studies using long‐term IFN maintenance therapy in 41, 34 and 35 patients, respectively 9–11 . In contrast to these studies, a multi‐centre Italian study evaluating IFN as adjuvant therapy (3mU s.c. thrice weekly) for 6 months following 2‐deoxycoformycin therapy did not show any difference in the proportion or duration of remissions 12 …”
Section: Discussionmentioning
confidence: 75%
“…Our results are similar to those from three previous studies using long‐term IFN maintenance therapy in 41, 34 and 35 patients, respectively 9–11 . In contrast to these studies, a multi‐centre Italian study evaluating IFN as adjuvant therapy (3mU s.c. thrice weekly) for 6 months following 2‐deoxycoformycin therapy did not show any difference in the proportion or duration of remissions 12 …”
Section: Discussionmentioning
confidence: 75%
“…Marotta et al randomized 145 patients that had a response to DCF (CR or PR) to receive IFN-a or not. The results showed that there were no differences between the two arms regarding improvement of response or progression free of disease [42]. …”
Section: Interferon-alphamentioning
confidence: 69%
“…Clinical indications IFNa Small cell lung carcinoma [4] Actinic keratoses [5] Behcet's disease [6] Mycosis fungoides [7] Discoid lupus erythematosus [8] Haemangiomas [9] Hairy cell leukaemia [10] Multiple myeloma [11] Hodgkin's lymphoma [12] Non-Hodgkin's lymphoma [13] IFNb…”
Section: Generic Namementioning
confidence: 99%